Muzyka i tanieс w wychowaniu międzykulturowym – polsko-ukraińskie sploty - Kisiel, Mirosław; Nikolai, Halyna (Chowanna, 2022)
The paper presents the idea of the research project Theory and Practice of Musicalization of Early Education Teachers in the Intercultural Dimension, the aim of which will be to obtain opinions from the surveyed teachers and trainees for the profession on the given topic and to forecast activities and develop effective solutions in the field of “good practices”.